The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.bioactmat.2021.05.029
|View full text |Cite
|
Sign up to set email alerts
|

A low dose cell therapy system for treating osteoarthritis: In vivo study and in vitro mechanistic investigations

Abstract: Mesenchymal stem cells (MSCs) can be effective in alleviating the progression of osteoarthritis (OA). However, low MSC retention and survival at the injection site frequently require high doses of cells and/or repeated injections, which are not economically viable and create additional risks of complications. In this study, we produced MSC-laden microcarriers in spinner flask culture as cell delivery vehicles. These microcarriers containing a low initial dose of MSCs administered through a single injection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 76 publications
1
28
0
Order By: Relevance
“…Along with this cell-based therapy, cell-free therapy using the secretome of MSCs is regarded as a promising therapeutic approach for OA [ 51 ]. Many researchers have co-cultured MSCs and chondrocyte cells in order to study the secretome of MSCs and their effect on OA [ 38 , 52 , 53 ]. They discovered that upon co-culturing with MSCs, the proliferation of chondrocyte cells increased, while the apoptosis decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Along with this cell-based therapy, cell-free therapy using the secretome of MSCs is regarded as a promising therapeutic approach for OA [ 51 ]. Many researchers have co-cultured MSCs and chondrocyte cells in order to study the secretome of MSCs and their effect on OA [ 38 , 52 , 53 ]. They discovered that upon co-culturing with MSCs, the proliferation of chondrocyte cells increased, while the apoptosis decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Some substances that are naturally present in the body may be valuable in preventing or treating osteoarthritis. Although most research is in its infancy, it is possible to use natural ingredients to heal injuries or speed up cartilage repair (18).…”
Section: The Effect Of Guava Fruit Hydroalcoholic Extract On Tnf-α Ge...mentioning
confidence: 99%
“…The high popularity of complementary and alternative drugs can be due to their advantages such as widespread availability, no side effects or low side effects, good effectiveness and low cost compared to synthetic drugs. Because osteoarthritis is an inflammatory disease associated with joint destruction, modulatory cytokines and nitric oxide produced by chondrocytes play a key role in disease progression (18).…”
Section: The Effect Of Guava Fruit Hydroalcoholic Extract On Tnf-α Ge...mentioning
confidence: 99%
“…Investigation of this in vivo observation showed that supernatants from co-culture of chondrocytes and MSCs in 3D constructs had fewer inflammatory factors than co-culture with MSCs in monolayers. An increased expression of genes related to chondrogenesis and ECM interactions were also observed, suggesting a high therapeutic potential of secretome when MSCs are cultured in 3D constructs [ 105 ]. Similarly, when MSC was encapsulated in alginate microbeads and co-cultured with patient-derived OA chondrocytes, paracrine factors induced a pro-regenerative microenvironment, increasing anabolic, proliferative, and anti-apoptotic processes [ 106 ].…”
Section: Application Of Secretomes For Cartilage Repairmentioning
confidence: 99%